2018
DOI: 10.1007/978-3-319-91635-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned with Laser Scanning Point Cloud Management in Hadoop HBase

Abstract: While big data technologies are growing rapidly and benefit a wide range of science and engineering domains, many barriers remain for the remote sensing community to fully exploit the benefits provided by these emerging powerful technologies. To overcome these barriers, this paper presents the in-depth experience gained when adopting a distributed computing framework -Hadoop HBase -for storage, indexing, and integration of large scale, high resolution laser scanning point cloud data. Four data models were conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The data encoding is a component within a complete data storage system that integrates the encoding with other components including data indices, search algorithms, and cache strategies. Readers may consult the authors' previous works for information explicitly on those other topics [6], [7]).…”
Section: Introductionmentioning
confidence: 99%
“…The data encoding is a component within a complete data storage system that integrates the encoding with other components including data indices, search algorithms, and cache strategies. Readers may consult the authors' previous works for information explicitly on those other topics [6], [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, SQL-on-Hadoop-based system have received much attention [48,49] for they provide the benefits of SQL in querying the data. However, Vo et al [17] note how Hadoop-based approaches work best when the task clearly lends itself to be run in parallel, such as treating a point cloud as a group of independent tiles. Moreover, as described in a benchmark [50], though offering better performance and scalability in querying a point cloud than PostgreSQL, the authors found out that configuring an SQL-on-Hadoop-based system (Spark SQL) for optimal performance can be daunting and indeed requires lots of memory.…”
Section: The Big Data Approachmentioning
confidence: 99%
“…Since we cannot rely on being able to keep the whole point cloud in memory, the main issue with point clouds remains that of indexing: how can we keep the index small enough, so that at least parts of it fits into memory? With RDBMS, we can reduce the index granularity [17] through the previously mentioned grouping of points into blocks or patches, but as pointed out in References [15,56], there is a cost to pay. Regarding queries, the implication is that individual points in a block are invisible to the query processor until the block is exploded into the original individual points.…”
Section: On Indexing Multidimensional Data: the B + Tree Indexmentioning
confidence: 99%
See 2 more Smart Citations